PENGERTIAN AKREDITASI SEKOLAH, DASAR PENYELENGGARAAN, DAN RUANG LINGKUP AKREDITASI SISTEM PERSEKOLAHAN - Nurul Masruni; Raisha Khotimah; Husnul Yaqin; Hilmi Mizani (EDUCATIONAL JOURNAL : General and Specific Research, 2026)
School accreditation is a primary instrument in the educational quality assurance system. This study aims to analyze the concept of school accreditation, its legal foundation, and its scope within the schooling system. Using a qualitative approach with a library research method, this study examines various national policies, international reports, and contemporary literatures. The results indicate that school accreditation has shifted from a compliance-based approach to a performance-based evaluation designed to foster a quality culture. In Indonesia, the legal basis for school accreditation is strongly rooted in Law No. 20 of 2003 and Government Regulation No. 57 of 2021, executed by the independent body BAN-PDM. Furthermore, the scope of accreditation comprehensively covers the eight National Education Standards spanning input, process, output, and outcome dimensions. This study concludes that school accreditation is a strategic policy instrument that functions not only for formal recognition but also to drive continuous improvement and public trust.